Stem Amaranth Yield in Response to Organic Manuring - Miah, MY; Roy, PK; Islam, MS; Fazal, KI (Journal of Environmental Science and Natural Resources, 2015)
Field investigations are important tools for confirmation of the effectiveness of the organic manures on crop yield. As different N sources, this work presents a comparative study of the effects of urea, cow dung and poultry manure on plant height, stem length and diameter, leaf length, breadth and number accompanied with the fresh weight of plant, stem, leaf coupling stem leaf ratio and gross yield of stem amaranth (Amaranthus tricolor Var. BARI Data 1). With an imposition of eight treatments, a field study was conducted at the farm of BSMRAU campus, Gazipur during February-April, 2007 in a Randomized Complete Block Design (RCBD). Treatments were control and seven N sources namely, urea (107 kg N ha-1), cow dung (23.75 t ha-1), poultry manure (9.3 t ha-1), half cow dung and half urea, half poultry manure and half urea, three fourth cow dung and one fourth urea and three fourth poultry manure and one fourth urea, respectively with four replications ensuring the 107 kg N ha-1 supply from all sources of N used. Compared with cow dung and poultry manure, urea resulted in higher plant height, broader stem length and diameter, more fresh weight of plant, stem and leaf accompanied with maximum gross yield. However, data on the studied parameters varied significantly (p< 0.05). So cow dung and poultry manure applied at 23.75 t ha-1 and 9.3 t ha-1, respectively were compatible to urea as N source for stem amaranth production. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22082 J. Environ. Sci. & Natural Resources, 6(2): 19-23 2013